Factors affecting the energy cost of level running at submaximal speed - Lacour, J.-R. (European Journal of Applied Physiology, 2015)
Metabolic measurement is still the criterion for investigation of the efficiency of mechanical work and for analysis of endurance performance in running. Metabolic demand may be expressed either as the energy spent per unit distance (energy cost of running, C r) or as energy demand at a given running speed (running economy). Systematic studies showed a range of costs of about 20 % between runners. Factors affecting C r include body dimensions: body mass and leg architecture, mostly calcaneal tuberosity length, responsible for 60-80 % of the variability. Children show a higher C r than adults. Higher resting metabolism and lower leg length/stature ratio are the main putative factors responsible for the difference. Elastic energy storage and reuse also contribute to the variability of C r. The increase in C r with increasing running speed due to increase in mechanical work is blunted till 6-7 m s-1 by the increase in vertical stiffness and the decrease in ground contact time. Fatigue induced by prolonged or intense running is associated with up to 10 % increased C r; the contribution of metabolic and biomechanical factors remains unclear. Women show a C r similar to men of similar body mass, despite differences in gait pattern. The superiority of black African runners is presumably related to their leg architecture and better elastic energy storage and reuse.